Recent Advances in the Regioselective Synthesis of Indoles via C–H Activation/Functionalization - Kumar, Inder; Kumar, Rakesh; Sharma, Upendra (Synthesis, 2018)
Indole is an important heterocyclic motif that occurs ubiquitously in bioactive natural products and pharmaceuticals. Immense efforts have been devoted to the synthesis of indoles starting from the Fisher indole synthesis to the recently developed C–H activation/functionalization-based methods. Herein, we have reviewed the progress made on the regioselective synthesis of functionalized indoles, including 2-substituted, 3-substituted and 2,3-disusbstituted indoles, since the year 2010.1 Introduction2 Metal-Catalyzed Synthesis of 2-Substituted Indoles3 Metal-Catalyzed Synthesis of 3-Substituted Indoles4 Metal-Free Synthesis of 3-Substituted Indoles5 Metal-Catalyzed 2,3-Disubstituted Indole Synthesis5.1 Metal-Catalyzed Intramolecular 2,3-Disubstituted Indole Synthesis5.2 Metal-Catalyzed Intermolecular 2,3-Disubstituted Indole Synthesis6 Metal-Free 2,3-Disubstituted Indole Synthesis6.1 N-Protected 2,3-Disubstituted Indole Synthesis6.2 N-Unprotected 2,3-Disubstituted Indole Synthesis7 Applications8 Summary and Outlook
Keywords: indoles; C–H activation; catalytic; metal-free; natural products